2020
DOI: 10.1177/1756284820942617
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic hepatitis C-associated cryoglobulinemia vasculitis at the era of direct-acting antivirals

Abstract: Hepatitis C virus (HCV) infection is responsible for both hepatic and extrahepatic manifestations. Before the era of direct-acting antivirals (DAA), cryoglobulinemia was related to HCV infection in 70–90% of cases. Observed in 30% to 40% of patients with hepatitis C, mixed cryoglobulinemia is mainly asymptomatic. Conversely, symptomatic cryoglobulinemia vasculitis (CV) can occur in 5–10% of patients with HCV-associated cryoglobulinemia. CV is a small-vessel systemic vasculitis, and organ damage results from ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Less than 5% of patients discontinue DAA treatment (79). Of note is that in the DAA era the mortality rate of HCV-CryoVas is less than 3% compared with 40 to 60% in the IFN era (79).…”
Section: Therapeutic Strategies 41 Hcv-related Cryoglobulinemic Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 5% of patients discontinue DAA treatment (79). Of note is that in the DAA era the mortality rate of HCV-CryoVas is less than 3% compared with 40 to 60% in the IFN era (79).…”
Section: Therapeutic Strategies 41 Hcv-related Cryoglobulinemic Vasculitismentioning
confidence: 99%
“…Less than 5% of patients discontinue DAA treatment (79). Of note is that in the DAA era the mortality rate of HCV-CryoVas is less than 3% compared with 40 to 60% in the IFN era (79). However, achievement of an SVR is necessary but not sufficient to achieve a complete immunological response, as 6 to 12 months following DAA therapy cryoglobulins remain present in about 50% of patients (Figure 5B).…”
Section: Therapeutic Strategies 41 Hcv-related Cryoglobulinemic Vasculitismentioning
confidence: 99%
“…Occasionally, extrahepatic-related autoimmune comorbidities such as cryoglobulinemia vasculitis can lead to the diagnosis of HCV infection[ 76 ]. Sustained eradication of HCV by IFN-α or DAA agents has shown to be beneficial for outcomes following these manifestations[ 78 , 79 ]. Notably, a prospective study with 9895 HCV-infected cases receiving DAA medications revealed that viral clearance is responsible for a significant decrease in HCV extrahepatic mortality[ 80 ].…”
Section: Extrahepatic Manifestations Of Human Hepatitis Viruses Infecmentioning
confidence: 99%
“…Anti-HCV therapy can follow the existing guideline as cryoglobulinemia does not specifically influence the choice of antiviral drug[ 138 ]. DAA agents alone induce SVR with less adverse events and are more effective than the combined IFN-α and ribavirin regimen in cryoglobulinemic vasculitis[ 79 ]. In a prospective multicenter study carried out in these patients, all achieved SVR with a 90% complete clinical response after DAA therapy for 12 wk or more[ 139 ].…”
Section: Human Hepatitis Viruses-associated Cryoglobulinemic Vasculitmentioning
confidence: 99%
See 1 more Smart Citation